2014
DOI: 10.5897/jphe2013.0613
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with outpatient health services in Hawassa University Teaching Hospital, Southern Ethiopia

Abstract: The level of patients' satisfaction is one among the mechanisms used in assessing the quality of health care services. This cross sectional study was conducted in Hawassa University Teaching Hospital to assess level of satisfaction of patients with outpatient health services and factors associated with it. Multiple logistic regression was used to assess the relationship between patients' satisfaction and possible predictors. Four-fifth (80.1%) of patients reported to be satisfied with the hospital's outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 13 publications
6
37
4
Order By: Relevance
“…The present study suggested that overall satisfaction level report is low compared to the report of the studies conducted in, Bahirdar Felege Hiwot Referral Hospital, and Hawassa University Teaching Hospital, which showed 52.8 and 80.1% respectively [3, 10, 11]. Concerning the privacy, almost 88% of the participants did not have private consultation.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The present study suggested that overall satisfaction level report is low compared to the report of the studies conducted in, Bahirdar Felege Hiwot Referral Hospital, and Hawassa University Teaching Hospital, which showed 52.8 and 80.1% respectively [3, 10, 11]. Concerning the privacy, almost 88% of the participants did not have private consultation.…”
Section: Discussioncontrasting
confidence: 72%
“…Evidence of variations in satisfaction with clinical practices in many health service institutions in Ethiopia have raised interest in measuring and improving healthcare service to enhance customer satisfaction [1]. According to the Donabedian model [2], three interrelated key domains namely structure, process, and outcome are important for identifying clients’ satisfaction which is by far an important indicator of service quality [2, 3]. Therefore, client satisfaction has been found to be the most useful tool for getting clients’ views on how to provide health care service.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was lower than research reports from Ethiopia (89.1%) in Jimma [7] and 80.1% in Hawassa [8], and abroad having overall patient satisfaction of 75.08% in Tertiary Care Hospital in Nagpur [4], 66.8% in Southeastern Nigeria [5]. These studies were about over all patient satisfaction, and our study was about satisfaction level of chronic illness patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Ethiopia previous studies showed that, there were differences in different localities with regard to the overall patients' satisfactions; 89.1% in Jimma [7], 80.1% in Hawassa [8], 54.1% in Harari region [9] and 18.0% of the patients at the public hospitals were very satisfied, 54.1% and 47.9% were just satisfied in Addis Ababa [10]. This study was done to assess the level Patients' Satisfaction in Felege Hiwot Referral Hospital, Bahir Dar City, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…on the other hand, the service centers provide the same kind of service for the patients; however, they cannot give the same quality of service. Therefore, all health service centers are obliged to provide all diagnostic and therapeutic services as much as possible due to the fact that the high level of patients' satisfaction relates to a better health (Gopal & Bedi, 2014;Farooq et al, 2012;Asefa et al, 2014;Gharibi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%